Industrialised building systems (IBS): it's attribute towards enhancing sustainability in construction / Nor Azmi Ahmad Bari ... [et al.] - Ahmad Bari, Nor Azmi; Mohd Yusuff, Rosnah; Ismail, Napsiah; Jaapar, Aini (Universiti Teknologi MARA Cawangan Selangor, 2018)
Greater Cairo Region (GCR) is the largest metropolitan area on the African continent and the Arab world. It accommodates 16.1 million inhabitants representing 19% of Egypt's total population. Today, critical urban issues arise from the sheer size of the metropolis GCR and from its population density. Traffic congestion is on the top of these issues. This research focuses on the significant role that hubs (Multi Modal Platforms) can play in enhancing the GCR transportation infrastructure. Ramses square area in Cairo is selected to demonstrate a systematic solution to solve the problems resulted from the interference of multi uses activities and transportation modes in central areas of capital cities.